2019
DOI: 10.1111/evo.13679
|View full text |Cite
|
Sign up to set email alerts
|

Testing the effect of early‐life reproductive effort on age‐related decline in a wild insect

Abstract: The disposable soma theory of ageing predicts that when organisms invest in reproduction they do so by reducing their investment in body maintenance, inducing a trade‐off between reproduction and survival. Experiments on invertebrates in the lab provide support for the theory by demonstrating the predicted responses to manipulation of reproductive effort or lifespan. However, experimental studies in birds and evidence from observational (nonmanipulative) studies in nature do not consistently reveal trade‐offs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 39 publications
(81 reference statements)
3
28
1
Order By: Relevance
“…This pattern is somewhat consistent with the results where the expression of traits related to reproduction (e.g. song activity, mate search, dominance) do not come with clear longevity costs in the wild in Gryllus campestris (Rodríguez-Muñoz et al, 2019). Longevity costs related to mating success seem to be more complex and depend on the degree (and form) of density-dependent plasticity in hourly mating success.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This pattern is somewhat consistent with the results where the expression of traits related to reproduction (e.g. song activity, mate search, dominance) do not come with clear longevity costs in the wild in Gryllus campestris (Rodríguez-Muñoz et al, 2019). Longevity costs related to mating success seem to be more complex and depend on the degree (and form) of density-dependent plasticity in hourly mating success.…”
Section: Discussionsupporting
confidence: 90%
“…This practically meant that we removed males from the focal male data set that were found, and marked, in the middle/end of the season (specifically, days 15-27 after the maturation of the first individual; n = 7 males with unknown age). Removal of males with unknown exact adult age was important as age affects many traits in our model species, including the sexual signaling and attractiveness (Rodríguez-Muñoz et al, 2019; Verburgt, Ferreira, & Ferguson, 2011), and thus had to be controlled for in our models. Notably, those males with unknown exact adult age were included when calculating local density.…”
Section: Methodsmentioning
confidence: 99%
“…We collected adult and subadult crickets from ten sites in Northern Spain (see Table 1) in late April and early May 2018 using burrow traps (for details on trapping see Rodríguez-Muñoz et al (2019a)). Five sites were at low altitude (84 ± 59m above sea level (mean ± SD)) and five sites were at high altitude (1148 ± 164m).…”
Section: Cricket Collection and Breedingmentioning
confidence: 99%
“…This principle is at the core of the theory of ageing, which predicts that, as reproduction is resource demanding, current reproduction is traded-off against future reproduction and survival, caused by a reduced investment into somatic protection and maintenance [2][3][4]. However, recent studies have sometimes revealed patterns of actuarial (decline in survival rate with age) and reproductive (decline in reproductive success with age) senescence rather contrasted with this prediction [5][6][7]. Since individuals may differ in both resource acquisition and resource allocation between traits, depending on individual and environmental quality, the cost of reproduction can remain undetected at the population level [8,9].…”
Section: Introductionmentioning
confidence: 99%